Water relations of Capsicum genotypes under water stress - Ismail, M.R.; Davies, W.J. (Institute of Experimental Botany, 1997)
Pepper species and cultivars, Capsicum annuum cv. Bell Boy, C. annuum cv. Kulai and C. frutescens cv. Padi, differing in drought tolerance were investigated for their water relations, stomatal responses and abscisic acid (ABA) content during water stress. C. frutescens cv. Padi exhibited a greater osmotic adjustment than C. annuum cultivars. Stomatal conductance of cv. Bell Boy was more sensitive to water stress than that of cvs. Kulai and Padi. In all pepper genotypes, stomatal closure was triggered in the absence of a large decrease in leaf water status. ABA content in xylem sap and leaf was higher in C. annuum cultivars compared to C. frutescens cv. Padi.